213k views
0 votes
Expand $3p^5q^3\left( 2pq + \frac{5}{(pq)^2} \right)$. Thank you so much i really need it

User Nithya
by
5.1k points

2 Answers

5 votes

Answer:

6p^6q^4+15p^3q

Step-by-step explanation:

We use the distributive property.

Expand $3p^5q^3\left( 2pq + \frac{5}{(pq)^2} \right)$. Thank you so much i really-example-1
User Illya
by
5.1k points
2 votes

Answer:
6p^6q^4 + 15p^3q

On a keyboard you would type 6p^6q^4 + 15p^3q

================================================

Work Shown:


3p^5q^3\left( 2pq + (5)/((pq)^2) \right)\\\\\\3p^5q^3\left( 2pq \right) + 3p^5q^3\left((5)/((pq)^2) \right)\\\\\\6p^6q^4 + (15p^5q^3)/( p^2q^2 ) \right)\\\\\\6p^6q^4 + 15p^3q\\\\

------------

Step-by-step explanation:

  • Step 2 used the distributive property.
  • Step 3 used the idea that a^b*a^c = a^(b+c), and also (ab)^c = a^c*b^c
  • Step 4 used the idea that (a^b)/(a^c) = a^(b-c)

User Alhalama
by
4.7k points